Querying the future - Agnieszka Pasieka (Sub\urban)
In my short contribution, I draw on my ethnographic research to show how far-right activists strive to address “the liberal question” and imagine future. I argue that the inspirations from fascism, and more specifically fascist conceptions of time, are central to these endeavors.